Energy Performance Certificates and Historic Apartment Buildings: A Method to Encourage User Participation and Sustainability in the Refurbishment Process. (3rd April 2019) - Berg, Fredrik; Donarelli, Anna
ABSTRACT: This article presents and discusses the challenges of refurbishing historic apartment buildings by correlating findings from research projects LEAF and CulClim. Our aim is to shed light on how residents can partake in and optimise the refurbishment process after energy performance certificates (EPC) have been conducted. The background is that historic apartment buildings are generally more complex than single family buildings with respect to the energy efficiency process as they often have multiple owners with different priorities. The case studies from Norway and Sweden have conceptually contrasting energy performance certificate (EPC) systems. Identified advantages and shortcomings concerning both systems are discussed. In Sweden, the restrained recommendation of measures can lead to national mitigation targets not being realised. In Norway, excessive and unqualified recommendations risk reducing the cultural heritage values of the existing building stock as well as having a negative environmental impact on greenhouse gas emissions. A bottom-up approach incorporating the resident's objectives is presented and discussed. Results suggest that improved EPC-systems and a broadened procedural approach to decision making will ease the process and improve the outcome of the refurbishment with respect to both energy and heritage aspects.